Regulation of neuronal excitability by release of proteins from glial cells - Igelhorst, Birte A. (Philos Trans R Soc Lond B Biol Sci, 2015)
Effects of glial cells on electrical isolation and shaping of synaptic transmission between neurons have been extensively studied. Here we present evidence that the release of proteins from astrocytes as well as microglia may regulate voltage-activated Na(+) currents in neurons, thereby increasing excitability and speed of transmission in neurons kept at distance from each other by specialized glial cells. As a first example, we show that basic fibroblast growth factor and neurotrophin-3, which are released from astrocytes by exposure to thyroid hormone, influence each other to enhance Na(+) current density in cultured hippocampal neurons. As a second example, we show that the presence of microglia in hippocampal cultures can upregulate Na(+) current density. The effect can be boosted by lipopolysaccharides, bacterial membrane-derived stimulators of microglial activation. Comparable effects are induced by the exposure of neuron-enriched hippocampal cultures to tumour necrosis factor-α, which is released from stimulated microglia. Taken together, our findings suggest that release of proteins from various types of glial cells can alter neuronal excitability over a time course of several days. This explains changes in neuronal excitability occurring in states of thyroid hormone imbalance and possibly also in seizures triggered by infectious diseases.